2014
DOI: 10.1242/dmm.016402
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced glucose tolerance in pancreatic derived factor (PANDER) knockout C57BL/6 mice

Abstract: Pancreatic-derived factor (PANDER; also known as FAM3B) is a uniquely structured protein strongly expressed within and secreted from the endocrine pancreas. PANDER has been hypothesized to regulate fasting and fed glucose homeostasis, hepatic lipogenesis and insulin signaling, and to serve a potential role in the onset or progression of type 2 diabetes (T2D). Despite having potentially pivotal pleiotropic roles in glycemic regulation and T2D, there has been limited generation of stable animal models for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…FAM3A plays important roles in regulation of hepatic and glucose metabolism via ATP-P2 receptor-mediated activation of Akt pathways independent of insulin (7). FAM3B (PANDER) exerts deleterious effects on pancreatic b-cell function (9,10) and hepatic insulin signaling (11)(12)(13)(14). To date, FAM3C, also known as interleukin-like epithelial-mesenchymal transition (EMT) inducer (ILEI), has been reported to be important in embryonic development, EMT, and the progression of some cancers (15)(16)(17).…”
mentioning
confidence: 99%
“…FAM3A plays important roles in regulation of hepatic and glucose metabolism via ATP-P2 receptor-mediated activation of Akt pathways independent of insulin (7). FAM3B (PANDER) exerts deleterious effects on pancreatic b-cell function (9,10) and hepatic insulin signaling (11)(12)(13)(14). To date, FAM3C, also known as interleukin-like epithelial-mesenchymal transition (EMT) inducer (ILEI), has been reported to be important in embryonic development, EMT, and the progression of some cancers (15)(16)(17).…”
mentioning
confidence: 99%
“…PANDER-deficient mouse livers exhibited lower hepatic TG content than wild type mice. Moreover, PANDER-deficient mice also had higher hepatic pAkt and pAMPK levels than wild type mice [114]. Inhibition of PANDER expression has been proposed to mediate the beneficial effects of aerobic swimming training on steatosis in obese mice [115].…”
Section: Liver-derived Pander In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…It is likely that insulin resistance, inhibition of AMPK activity and upregulation of PPARγ also contribute to PANDER-induced lipid deposition in the liver [111,112,114]. Wilson et al reported a secretory form of PANDER in the medium of cultured hepatocytes with PANDER overexpression [112].…”
Section: Liver-derived Pander In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Hepatic PANDER overexpression promotes gluconeogenesis and lipogenesis, whereas hepatic PANDER silencing ameliorated fatty liver and hyperglycemia in obese mice . PANDER knockout (PANKO) mice exhibit increased hepatic insulin sensitivity . In humans, increased circulating PANDER levels have been reported to be associated with pancreatic β cell dysfunction, hyperglycemia and insulin resistance in various races .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 PANDER knockout (PANKO) mice exhibit increased hepatic insulin sensitivity. 15,16 In humans, increased circulating PANDER levels have been reported to be associated with pancreatic β cell dysfunction, hyperglycemia and insulin resistance in various races. [17][18][19] Overall, these clinical and experimental studies had established that PANDER plays important roles in the regulation of glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%